Triaging, emergency surgical management, and nutritional rehabilitation of a case of acute on chronic mesenteric vascular ischemia - Jeena Raju Kudunthail,; Asif Ansari,; Waqar Ansari,; Kushagra Rahul Srivastav, (Indian Journal of Case Reports, 2021)
Mesenteric vascular ischemia (MVI) is a leading cause of short bowel syndrome (SBS). There is no uniformity in management protocol for MVI and there lacks consensus on when and how to operate. In this report, we present a case of type 2 SBS following extensive resection of bowel managed postoperatively with a combination of enteral nutrition (EN) and parenteral nutrition (PN). We used Acute Physiology and Chronic Health Evaluation 2 scoring system along with intraoperative findings to stratify our case and proceed with resection and anastomosis of the bowel in the same sitting. The total PN was started from post-operative day 1 along with micronutrients and vitamin supplements. We were able to taper PN to supplement 30% of the daily caloric requirement and 70% by EN by the end of 8 weeks. Triaging the patient, prompt surgery, early institution of PN along with EN, micronutrients, and vitamin supplements proved to be the key for improved outcomes.